Cultural Differences in Language Use. How Culture Shapes Language, Communication as well as learning styles (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Language learning is inherently tied to cultural context, which significantly influences both the language itself and the teaching methodologies employed in educational settings. This article explores how various cultural backgrounds shape language learning experiences and how they inform teaching styles. By analyzing the relationship between culture, language acquisition, and pedagogy, this study underscores the importance of culturally responsive teaching in fostering effective language learning